1981
DOI: 10.2307/3759499
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nutritional Relationship of Larval Aedes aegypti (Diptera: Culicidae) with Smittium culisetae (Trichomycetes)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This fungus grows prolifically in the hindguts of the larvae. However, in this case, Horn & Lichtwardt (1981) concluded that this fungus provides essential nutrients needed for the growth of the larvae, suggesting a mutualistic relationship. However, these relationships need to be precisely defined by "Omics" molecular studies.…”
Section: Discussion and Future Prospectsmentioning
confidence: 84%
See 1 more Smart Citation
“…This fungus grows prolifically in the hindguts of the larvae. However, in this case, Horn & Lichtwardt (1981) concluded that this fungus provides essential nutrients needed for the growth of the larvae, suggesting a mutualistic relationship. However, these relationships need to be precisely defined by "Omics" molecular studies.…”
Section: Discussion and Future Prospectsmentioning
confidence: 84%
“…Furthermore, the precise roles of symbionts are often not even known. An interesting study of the symbiotic relationship between one putative host (larval Aedes aegypti, Diptera) and one putative commensal fungus (Smittium culisetae, Trichomycetes) was conducted by Horn & Lichtwardt (1981). This fungus grows prolifically in the hindguts of the larvae.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…quinquefasciatus. Smittium culisetae may benefit mosquito larvae raised under conditions of nutritient deficiency (Horn and Lichtwardt 1981). In contrast, Sm.…”
Section: Smittium Culicis Maniermentioning
confidence: 97%
“…The roles and importance of Trichomycetes in pelagic food webs are not known at all. Horn and Lichtwardt (1981) have demonstrated, experimentally, that the Trichomycetes Smittium culisetae in the hindgut of the aquatic mosquito larvae Aedes aegypti could serve as a source of essential elements for insect growth, primarily of sterols and B-vitamin (Lichtwardt et al 2003). Similar to the case of fungi that can improve the palatability of leaves for macroinvertebrates in wetlands and running waters (Suberkropp et al 1983), mutualistic Trichomycete fungi may be able to improve the assimilation of recalcitrant compounds directly in the gut of their hosts.…”
Section: Mixophyes Fasciolatusmentioning
confidence: 99%